Membangun Kesetaran Relasi Suami Isteri Dalam Keluarga Menurut Al-Qur’an - Khusnul Khotimah, Umi (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2022)
Humans are noble creatures created in the most perfect form. In accordance with the dignity of man as the most important and noble creature, the method of channeling his biological needs must be honorable. This method is none other than through the institution of marriage. Humans who channel their biological needs without going through a legal marriage, then they have willingly sacrificed their human dignity. The Qur'an mentions that couples in marriage must be of different types, namely l aki-male and female. Although different in gender, the concept of pairing in Islam is equality, not domination of one party over the other. The division of tasks and authority in pairing is a union of two forces to complement all forms of deficiencies. This is what should be practice in family life, so that the purpose of marriage can be achieved according to expectations.